2012
DOI: 10.3389/fneur.2012.00125
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Functions in Ataxia with Oculomotor Apraxia Type 2

Abstract: Background: Ataxia with oculomotor apraxia type 2 (AOA2) is characterized by cerebellar atrophy, peripheral neuropathy, oculomotor apraxia, and elevated serum alpha-fetoprotein (AFP) levels. The disease is caused by a recessive mutation in the senataxin gene. Since it is a very rare cerebellar disorder, no detailed examination of cognitive functions in AOA2 has been published to date. The aim of the present study was to investigate the neuropsychological profile of a 54-year-old patient with AOA2. Methods: A b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…This study has limitations. We focused on serial ordering in working memory in PD, but the serial ordering problem also exists in other cognitive domains [27,28] and in other neurological diseases [29,30]. However, few patient studies included a systematic analysis of serial ordering errors.…”
Section: Discussionmentioning
confidence: 99%
“…This study has limitations. We focused on serial ordering in working memory in PD, but the serial ordering problem also exists in other cognitive domains [27,28] and in other neurological diseases [29,30]. However, few patient studies included a systematic analysis of serial ordering errors.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, these studies provided only limited evidence for disentangling sequence-specific learning from more general psychomotor impairments. For example, the BD patients in Chrobak et al's (2015) study did not show speed-up during the sequence blocks at all that could be caused either by a deficit in general skill learning and/or in sequence-specific learning (Borbély-Ipkovich et al, 2014;Klivenyi et al, 2012). While Exner et al ( 2009) report some general speed-up besides the deficit in sequence learning in the MDD patients, the Naismith et al studies did not report data in that regard (Naismith et al, 2006;Naismith et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Studies with SRT found impaired learning during a depressive episode in MDD (Exner, Lange, & Irle, 2009;Naismith, Hickie, Ward, Scott, & Little, 2006) as well as in BD (Chrobak et al, 2015). However, these studies had a limited capacity to disentangle sequence-specific learning from more general psychomotor impairments: if patients do not show RT improvement during the sequence blocks at all, then no RT rebound can be expected on the random block (Borbély-Ipkovich, Janacsek, Németh, & Gonda, 2014;Klivenyi et al, 2012). Hence, based on these studies, one cannot conclude whether implicit learning of sequences is impaired or intact in depression.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, both siblings have not developed any cognitive impairment that has interfered with social functioning, although formal neuropsychiatric testing could not be obtained. Neuropsychiatric testing of a single AOA2 patient suggested that deficits in executive function, working memory and implicit sequence learning could be part of a cerebellar cognitive process in AOA2 [23]. Recent studies suggest that the cerebellum may have more influence on cognition than previously thought, and it would be interesting to investigate this further in a larger cohort of AOA2 patients with cerebellar degeneration and extended longevity [24,25].…”
Section: Discussionmentioning
confidence: 99%